Pola Komunikasi pada Hubungan Pernikahan dengan Pria yang Berusia Lebih Muda dalam Budaya Patriarki - Yunusiah, Septia; Ratri Rahmiaji, Lintang (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
Practice of patriarchy is still so viscous on Indonesian society. Even on a marriage life, Indonesian believe that husband has a dominant social role than wife. That issue become interesting when a man married an older woman. Remembering that husband role is dominant in Indonesian believe, this research is focus on how is Communication Patterns on Marriage Relationship with Younger Man in Patriarki Culture The result of this research shows that different ages, in this case is when husband is younger, did not affect the process of communication between husband and wife. Even though one of the research subject shows that they have a communication problem in their marriage life, that problem did not come from age differential between two of them, but from their social status and some culture that give a women domination on a marriage life. A men who marry older woman tend to have a good quality of marriage life same as other married couples. Husband keep dominating almost all aspect on marriage life such as conflict, discussion, even on daily talk. However, some couples also shows that wife is dominating their marriage life, but it was caused by difference of their social status and the husband character not by the age differential.